COMPARISON BETWEEN BHARTIY SAKSHY ADHINIYAM AND EVIDENCE ACT 1872 - Dimpal Goyal; Dr. Anamika Yadav (Innovative Research Thoughts, 2024)
India's legal system undergoes a major overhaul as the Indian Evidence Act, 1872, gives way to the Bhartiya Shakshya Adhiniyam. Analyzing their main clauses, revisions, and effect on the legal system, this paper seeks to contrast the two legislative instruments. The study underlines important changes in evidence collecting, admissibility, digital evidence, and procedural adjustments implemented under the new law. It also looks at the difficulties and ramifications of the change as well as India's future chances for bettering her evidentiary laws. Long the pillar of India's legal system, the Indian Evidence Act, 1872 directs court procedures addressing admission, relevance, and weight of evidence. But the Bhartiya Sakshya Adhiniyam seeks to modernize and solve the constraints of the current system in view of changing legal demands and technical developments. Focusing on their effects on legal procedures—particularly in the digital age—this paper contrasts these two legislative acts.